Higher-resolution biostratigraphy for the kinta limestone and an implication for continuous sedimentation in the paleo-tethys, western belt of peninsular Malaysia - Tsegab, H. (TUBITAK, 2017)
The paleogeography of the juxtaposed Southeast Asian terranes, derived from the northeastern margins of Gondwana during the Carboniferous to Triassic, resulted in complex basin evolution with massive carbonate deposition on the margins of the Paleo-Tethys. Due to the inherited structural and tectonothermal complexities, discovery of diagnostic microfossils from these carbonates has been problematic. This is particularly the case for the Kinta Limestone, a massive Paleozoic carbonate succession that covers most of the Kinta Valley in the central part of the Western Belt of Peninsular Malaysia. Owing to the complex structural and igneous events, as well as extensive diagenetic alterations, establishing precise age constraints for these carbonates has been challenging. Furthermore, the sedimentation history of these deposits has been masked. Three boreholes, totaling 360 m thickness of core, were drilled at either end of the Kinta Valley on a north-south transect through sections with minimal thermal alteration. The sections are composed chiefly of carbonaceous carbonate mudstone with shale and siltstones beds, in which the carbonates were sampled for microfossils. Five hundred conodont elements were extracted. Nine diagnostic conodont genera and 28 age diagnostic conodont species were identified. The identification of Pseudopolygnathus triangulus triangulus and Declinognathodus noduliferus noduliferus indicated that the successions ranged from Upper Devonian to upper Carboniferous. Further analysis and establishment of stage-level datum that range from the Famennian to Bashkirian (Late Carboniferous) enabled detection of continuous sedimentation and improved age constraints in undated sections of the Kinta Limestone. This higher-resolution conodont biostratigraphy suggests a prevalence of continuous carbonate deposition during the Early Devonian to Late Carboniferous in the Paleo-Tethys. Thus, the identification of diagnostic conodont species for the first time from subsurface data in the area has helped improve the biostratigraphic resolution and establishes depositional continuity of the Kinta Limestone. These data could provide clues to the Paleo-Tethys paleogeographic reconstruction and paleodepositional conditions, and could establish higher temporal resolution correlation than previously attempted. © TÜBİTAK.